PERILAKU KONSUMEN MINUMAN KOPI DI QALU COFFEE KOTA BANDAR LAMPUNG - Riyanti, Linda; Indriani, Yaktiworo; Kasymir, Eka (Lampung University, 2024)
This research aims to determine the behavior of coffee beverage consumers in Qalu Coffee. The research method is a survey. The number of respondents in this research is 60 Qalu Coffee consumers. Data collection was carried out in November-December 2023. The data in this research was analyzed quantitatively descriptively using Fishbein's multiattribute model, Customer Satisfaction Index (CSI), loyalty pyramid, and multiple linear regression. The results showed that consumer attitudes towards Qalu Coffee coffee drinks were in a good category. The average number of consumer purchases is 2 cups with the number of purchases per visit as much as 1 cup, the average frequency of purchases is 2 times/month, the most purchased coffee drink flavor variant is Qopsu Aren, and most consumers come at night to hang out, the most consumer visit time is between 3-4 hours, and the most widely used vehicle is a motorcycle. Consumer satisfaction with Qalu Coffee coffee drinks is in the very satisfied category. Consumer loyalty to Qalu coffee drinks is quite good with the greatest value at the level of liking the brand. Factors that have a real influence on the number of purchases are the price of non-coffee drinks, income, and taste. Key words: attitude, coffee, loyalty, satisfaction